Odpowiedzi

2010-03-23T16:29:12+01:00
A) -4x - 7 - 3x + 7=-7x
b) x - 2xy + 1/2x - 1/3xy
c) -x² + y² - 2x² - 2y²=-3x²-y²
d) -x² + 2x - 3x + x²=-x
e) 4x + 4 - 7x - 1/2=-3x+3½
f) -2ab + 12a - 4ab - 16a=-4a-6ab
1 1 1
2010-03-23T16:29:22+01:00
A) -4x - 7 - 3x + 7=-7x
b) x - 2xy + 1/2x - 1/3xy= 1i1/2x -2i1/3xy
c) -x(kwadrat) + y(kwadrat) - 2x(kwadrat) - 2y(kwadrat)= -3x(kwadrat)-y(kwadrat)
d) -x(kwadrat) + 2x - 3x + x(kwadrat)= -x
e) 4x + 4 - 7x - 1/2=-3x+3i1/2
f) -2ab + 12a - 4ab - 16a =-4a-6ab

licze na naj!
1 5 1